Retirement Planning: Impact of Financial Literacy and Future Orientation pada Pekerja di Kabupaten Bekasi - Erin Soleha; Trianto Trianto (Global Leadership Organizational Research in Management, 2025)
Retirement represents a crucial period in the existence of every individual that requires careful financial planning. This study aims to examine the influence of partial financial literacy on pension fund planning for workers in Bekasi Regency and partial future orientation on pension fund planning for workers in Bekasi Regency. The research method employed involved a sample of 100 employees in Bekasi Regency.. The method employed for gathering data was a questionnaire. The collection of samples approach employs probability sampling through a staightforward random sampling technique. The analysis methods used were validity, reliability test, t-square and R-square test. The analysis tool used is PLS (Partial Least Square) where the processing uses Smart PLS 4.0 software. The study’s findings indicated that financial literacy did not influence pension fund planning  for workers in Bekasi Regency with a p value of 0.164, future orientation had a significant effect on pension fund planning for workers in Bekasi Regency with a p value of 0.000. The R Square value of the results of this study is 33.9%. This study is anticipated to deliver the  development of research knowledge in the field of financial science related to pension fund planning and for workers in Bekasi Regency may be utilized in an attempt to enhance pension fund planning. Advice for workers in Bekasi Regency to improve financial literacy, future orientation and education about the importance of pension fund planning. The more aware and motivated workers are about their financial needs in retirement, the more likely they are to plan for retirement well. It is anticipated for the upcoming researcher to delve deeper into alternative factors that affect pension fund planning, further increase the research sample and broaden the range od the research subject.